Management of Educational Facilities and Infrastructure: Efforts to Optimize the Learning Process at MA Nurul Fattah Lampung - Asep Irawan; Mela Apristianti; Lutfiatul Hidayah (Civiliza Publishing, Indonesia., 2026)
This research is motivated by the problem of the gap between infrastructure standard regulation and managerial practices in the field. At MA Nurul Fattah Lampung, facility management is still reactive and the inventory has not been digitized, so it often creates administrative obstacles that have the potential to reduce the quality of learning. The main objective of this research is to evaluate the practice of facilities and infrastructure governance in order to realize the optimization of a quality learning process. The method used was qualitative descriptive, with data collection through observation, in-depth interviews with seven key informants, and documentation studies. The results of the study found that empirically, well-maintained physical infrastructure transforms into a